Institutions, experiences and inflation aversion - Michael Berlemann; Sören Enkelmann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
Are preferences exogenously given? Or do individual tastes and values evolve endogenously within a particular socio-economic environment? In this paper, we make use of a natural experiment to analyse the role of inflation experiences and institutions in the formation of individual inflation preferences. In particular, we exploit the division of post-war Germany to investigate to what extent the factual non-experience of inflation and 40 years of Communism have affected inflation preferences in East and West Germany. We find that historical experiences have a significant and long-lasting effect on people's preferences. Due to their specific political and economic background, East Germans are significantly more inflation averse than West Germans, even 20 years after reunification.
Keywords: E02; E31; P22; 330; endogenous preferences; inflation aversion; natural experiment; Germany